MODEL DISTRIBUSI KERAJINAN KREATIF JEMBER MENUJU PASAR INTERNASIONAL - Muhsyi, Abdul; Fauziyyah, Salma; Khusna, Khanifatul; Mirzania, Alif (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2021)
The creative industry is one of the industries that currently supports the Indonesian economy. The purpose of this study is to formulate the distribution model of Jember's creative industry towards the international market. This study is quantitative-descriptive research conducted in Jember using SMEs as population. Furthermore, samples were taken by using a non-probability sampling technique with a convenience sampling method. The analytical tool used in this study was a fishbone diagram. The results of the fishbone diagram analysis showed several causes of SMEs growth problems such as the lack of HR skills in foreign languages, the inadequate of sophisticated technology in business, and the minimal amount of business capital. The inappropriate adoption of the technology was then identified as the root cause of the problem. Thus, the distribution model for the creative industry to increase competitiveness in the international market is the technology application in every element of the SMEs. Keywords: creative industry, distribution model, fishbone diagram, international market